High Similarity between Distantly Related Species of a Plant SINE Family Is Consistent with a Scenario of Vertical Transmission without Horizontal Transfers. (19th July 2016) - Fawcett, Jeffrey A.; Innan, Hideki
Abstract: Many transposable element (TE) families show surprisingly high levels of similarity between distantly related species. This high similarity, coupled with a "patchy" phylogenetic distribution, has often been attributed to frequent horizontal transfers of TEs between species, even though the mechanistic basis tends to be speculative. Here, we studied the evolution of the Au SINE (Short INterspersed Element) family, in which high similarity between distantly related plant species has been reported. We were able to identify several copies present in orthologous regions of various species, including species that diverged ∼90 Ma, thereby confirming the presence of Au SINE at multiple evolutionary time points. We also found that the Au SINE has been degenerating and is en route to disappearing in many species, indicating that the loss of Au SINE is common. Our results suggest that the evolution of the Au SINE can be readily explained by a scenario of vertical transmission without having to invoke hypothetical scenarios of rampant horizontal transfers. The Au SINE was likely present in the common ancestor of all angiosperms and was retained in some lineages while lost from others. The high level of conservation is probably because the sequences were important for ensuring their transpositional activity. This model of TE evolution should provide a basic framework for understanding the evolution of TEs in general.